Development of a critical-creative socioscientific instrument for prospective science teachers - I. Irwandani; Agus Suyatna; Een Yayah Haenilah; Dina Maulina; Anggun Septi Rahayu (Research and Development in Education (RaDEn), 2024)
The current educational challenges highlight a lack of focus on developing critical and creative thinking skills, especially related to socioscientific issues such as biodiversity. Existing learning systems tend to center on knowledge transfer, leaving many prospective teachers feeling underprepared to foster these skills in their classrooms. This underscores the need for an effective instrument to develop critical and creative thinking skills within a socioscientific context​. This study aims to develop the Critical-Creative Development Socioscientific Instrument (CCSI) tailored for assessing students' critical and creative thinking skills on socioscientific issue. This research is Research and Development (RnD) development research which refers to the ADDIE development model. The type of research used is mixed methods research with an embedded experimental model design. CCSI was meticulously validated by experts in the field, with five validators for the model and research instruments. The validation process demonstrated high levels of content and construct validity, with final percentages of 88.80% and 91.20%, respectively. The results indicate that the CCSI is "Very Valid" and "Appropriate to Use" as a tool for enhancing and assessing 21st-century skills, particularly in the context of socioscientific issue. This instrument is therefore recommended for use in educational settings where the development of critical and creative thinking is essential.